For debate: health service support planning for large-scale defensive land operations (part 2). Issue 3 (19th June 2019) - Bricknell, Martin; Finn, A; Palmer, J
Abstract : This is the second of two articles that considers the medical planning implications of large-scale defensive military operations. This paper describes a unified approach to theatre level health services support planning based on four phases: collection, hospitalisation, evacuation and reception. It highlights the need for a modular and agile system of medical capability building blocks that can be grouped together for specific military medical challenges. It also reintroduces the concepts of mass casualty and the medical reserve. These two papers are designed to encourage debate around how we should be organised to face the new challenges of health services support in potential peer-on-peer military operations.